2019
DOI: 10.1371/journal.pone.0212774
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the tree shrew gut virome

Abstract: The tree shrew ( Tupaia belangeri ) has been proposed as an alternative laboratory animal to primates in biomedical research in recent years. However, characteristics of the tree shrew gut virome remain unclear. In this study, the metagenomic analysis method was used to identify the features of gut virome from fecal samples of this animal. Results showed that 5.80% of sequence reads in the libraries exhibited significant similarity to sequences deposited in the viral reference database (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
5
3
Order By: Relevance
“…Although the liver and gut are well-known bacterial niches in vertebrates [ 16 ], bacteriophages represented no more than 20% of the assigned contigs in our samples, suggesting that eukaryotic viruses may prevail in fish digestive organs [ 17 ]. This strongly differs from observations in other vertebrates such as birds and mammals, where phages were found to be predominant within the gut microflora [ 18 , 19 , 20 ]. However, Ramírez-Martínez et al (2018) [ 21 ] also demonstrated that eukaryotic viruses were dominant in the fecal virome of various wild migratory duck species.…”
Section: Resultscontrasting
confidence: 91%
“…Although the liver and gut are well-known bacterial niches in vertebrates [ 16 ], bacteriophages represented no more than 20% of the assigned contigs in our samples, suggesting that eukaryotic viruses may prevail in fish digestive organs [ 17 ]. This strongly differs from observations in other vertebrates such as birds and mammals, where phages were found to be predominant within the gut microflora [ 18 , 19 , 20 ]. However, Ramírez-Martínez et al (2018) [ 21 ] also demonstrated that eukaryotic viruses were dominant in the fecal virome of various wild migratory duck species.…”
Section: Resultscontrasting
confidence: 91%
“…Despite significant progress in the understanding of bacteriophage ecology in the human gut, data on other animal species are scarce. Although a significant number of metagenomic datasets from various species have been published [29] , [30] , [31] , [32] , the vast majority of these studies focus on the detection and interpretation of animal viruses, and bacteriophages have not been given significant attention. Only a few studies give emphasis to bacteriophage diversity in these samples, although this is limited to identifying differences between healthy and diseased states in rhesus monkeys [33] , [34] or specifically focusing on the diversity of ssDNA viruses [35] .…”
Section: Introductionmentioning
confidence: 99%
“…A major limitation of metatranscriptomics is that the true host range of many viruses often cannot be determined. Cloacal swabs and faecal samples are particularly challenging to identify viral-host associations as a high proportion of the total viral sequences identified are often dietary-related (33,4042). Indeed, 48 of the 49 novel viruses identified in this study were likely dietary-related and, consequently, the hosts of these viral sequences remain unclear.…”
Section: Discussionmentioning
confidence: 99%